Impact of sociodemographic and behavioral factors on the prevalence of overweight and obesity in schoolchildren - Dartagnan Pinto Guedes; Jaime Tolentino Miranda Neto; Maria João Almeida; António José Rocha Martins e Silva (Universidade Federal de Santa Catarina, 2010)
This study analyzed the impact of sociodemographic and behavioral factors on theprevalence of overweight and obesity in a representative sample of schoolchildren from MontesClaros, Minas Gerais, Brazil. The sample consisted of 2849 children and adolescents (1457girls and 1392 boys), ranging in age from 6 to 18 years. Overweight and obesity were definedbased on body mass index according to the cut-off values for gender and age suggested by theInternational Obesity Task Force (IOTF). The prevalence rates in the different strata associatedwith sociodemographic and behavioral factors were compared by logistic regression using adjustedodds ratios. The prevalence of overweight and obesity was 19.7% and 4.8%, respectively,among girls, and 14.7% and 2.8% among boys. The results show that, although the prevalenceof overweight and obesity is similar to estimates observed in other Brazilian regions and smallerthan those found in more industrialized areas, the proportion of schoolchildren who presentedoverweight and obesity is a matter of concern. The main sociodemographic and behavioralfactors associated with the occurrence of overweight were economic status, educational level ofthe parents, number of siblings, school menu, distance and means of transportation betweenhome and school, paid work, and leisure-time activity. The data show an urgent need for theimplementation of educational intervention programs designed to promote physical activity andadequate dietary habits.